A study of some aspects of selection for the fertility of New Zealand Romney ewes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science - Clarke, J. N. (Massey University, 1963)
No abstract
Keywords: Romney sheep; Romney Marsh sheep; Sheep reproduction; Sheep fertility